CPC 29 Ativo biológico: uma contribuição à mensuração do valor justo do ativo biológico florestal - Quirino, Mauro (2011)
It is considered as the main accounting objective, since its origin, to provide the users of financial statements with information to support them to make decisions. In order to achieve this objective in an efficient way the fair value accounting has been considered as a measurement alternative of selective assets, such as biological. The main characteristics of such asset are the biological transformation which comprises the processes of growth, degeneration, production and procreation that cause qualitative or quantitative changes. Therefore, it is understandable that measurement models based on historical cost do not reflect the real asset value and also do not measure in an efficient way the management performance on his/her role of manage the asset and the fair value could close this gap. As the quoted market price in an active market for a biological asset is the most reliable basis for determining the fair value of that asset, this paper aims to analyze the aspects related to the existence of active market for forest assets. Although there are limitations due to the limited wide of this analyze, it is not possible to say for sure that such market does not exist, but there are strong indications, on this actual stage of economic sector, that there is not active market for timber in this country. As an alternative for the lack of reliable market-basis prices for the measurement of the forest value, a discounted cash flow model will be presented in details. The choice of discounted cash flows model, out of other alternatives, is based on the fact that the majority of the forestry companies are using this tool